Dari Liturgi Baptisan menuju Liturgi Kehidupan: Menjadi Gereja bagi Perempuan Korban Kawin Tangkap - Irene Umbu Lolo (KENOSIS: Jurnal Kajian Teologi, 2020)
This article is a feminist liturgical imagination that aims to provide a recovery space for women victims of sexual violence. With the background of women experience as victims of marriage by abduction, this paper presents imaginative theological thoughts using the views of Ruether and Berger in the framework of providing an ecclesiastical ritual in favor of women victims. The church must stand with women victims of sexual violence. The support of the church can be shown through the provision of a liturgical space where women victims can share their experiences and at the same time reclaim one of the important symbols in the Christian liturgy, namely water as a sacred symbol of restoration. This ecclesiastical ritual is a space for women victims to show reversal movements, from circumstances and events where water marks past experiences of violence, to circumstances and events where water marks the present and future experience of healing. AbstrakTulisan ini merupakan suatu imajinasi liturgi feminis yang bertujuan menyediakan ruang pemulihan bagi perempuan korban kekerasan seksual. Dengan dilatari oleh pengalaman korban kawin tangkap, tulisan ini menyuguhkan pemikiran imajinatif teologis dengan menggunakan pandangan Ruether dan Berger dalam kerangka menyediakan suatu ritual gerejawi yang berpihak pada perempuan korban. Gereja mesti berdiri bersama perempuan korban kekerasan seksual. Keberpihakan gereja itu dapat ditunjukkan melalui penyediaan ruang liturgis dengan mana perempuan korban dapat membagi pengalamannya sekaligus mengklaim kembali salah satu simbol penting dalam liturgi Kristen yaitu air sebagai simbol sakral yang memulihkan. Ritual gerejawi ini merupakan ruang bagi perempuan korban untuk menunjukkan gerakan berbalik arah, dari keadaan dan peristiwa di mana air menandai pengalaman kekerasan di masa lampau, menuju keadaan dan peristiwa di mana air menandai pengalaman pemulihan di masa kini dan masa yang akan datang.